The effects of secondhand smoke on respiratory pathology, sensitization and development of allergic diseases in young children (literature review) - N.V. Kotova; O.O. Starets; D.A. Kovalenko (Zaslavsky O.Yu., 2021)
The prevalence of active smoking in Ukraine significantly exceeds the worldwide average, which is certainly a risk factor for children to be exposed to secondhand smoke. The article provides literature data and presents a modern view on the problem of secondhand tobacco smoke impact on the child population. In pediatric practice, the pathological impact of secondhand smoke on the child's health is significant at the stage of its fetal development. Historical data convincingly prove the connection between the antenatal effect of secondhand smoke and the increased risk of perinatal losses and risks of pregnancy - miscarriage, stillbirth, and premature birth. As early as the 1960s and 1970s, scientific evidence was obtained for an association between the effects of tobacco smoke and the risk of sudden infant death syndrome. Children are most vulnerable to the negative effects of tobacco smoke at an early age because they have closer and longer contact with their parents, especially their mothers. Many studies have found an association between the effects of secondhand smoke and airway pathology (bronchitis, pneumonia), as well as an increase in the severity of respiratory syncytial viral infection (bronchiolitis). Numerous literature data indicate an association between the effect of passive smoking and the frequency and severity of oral cavity (dental caries) and middle ear (recurrent and chronic otitis, middle ear effusion) pathology. Many studies have shown the effects of secondhand smoke on the development and severity of bronchial asthma in children, but scientific data on the causal relationship of tobacco smoke with other allergic diseases (atopic dermatitis, allergic rhinitis, and food allergies), which are common in young children and preceded bronchial asthma in the "atopic march, are more limited and contradictory. The literature was searched using the PubMed database.